Two-branch 3D convolutional neural network for motor imagery EEG decoding. (13th August 2021) - Yang, Lie; Song, Yonghao; Jia, Xueyu; Ma, Ke; Xie, Longhan
Abstract: Objective. The original motor imagery electroencephalography (MI-EEG) data contains not only temporal features but also a large number of spatial features related to the distribution of electrodes on the brain. However, in the process of MI-EEG decoding, most of the current convolutional neural network (CNN) based methods do not make the utmost of the spatial features related to electrode distribution. Approach. In this study, we adopt a concise 3D representation for the MI-EEG data to take full advantage of the spatial features and propose a two-branch 3D CNN (TB-3D CNN) for the 3D representation of MI-EEG data. First, the spatial and temporal features of the input 3D samples are extracted by the spatial and temporal feature learning branches, respectively, to avoid the mutual interference between the temporal and spatial features. Then, the central loss is introduced into the TB-3D CNN framework to further improve the MI-EEG decoding accuracy. And a 3D data augmentation method based on the cyclic translation of time dimension is proposed for the 3D representation method to alleviate the overfitting problem. Main results. Some experiments are conducted on the famous BCI competition IV 2a dataset to evaluate the effectiveness of the proposed MI-EEG decoding method. The experimental results comparison with some state-of-the-art methods demonstrates that the average accuracy of our method is 4.42% higher than that of the best of the comparative methods. Significance. The proposed MI-EEG decoding method has great promise to improve the performance of motor imagery brain-computer interface system.